A Convergent Approach to the Forskolin Skeleton - Ononiwu, Fortune O.; Wang, Bo; Totah, Nancy I. (Synlett, 2024)
A convergent approach to the forskolin skeleton is described. Assembly of a simplified tricyclic framework is achieved in a single step via the dihydropyrone Diels–Alder reaction. Selective manipulation of the resulting cycloadduct, in conjunction with an unusual equilibration of the C8 stereocenter, provides access to scaffolds that differ in relative stereochemistry at both the A/B and B/C ring junctions.
Keywords: Diels–Alder reaction; fused ring systems; regioselectivity; diastereoselective synthesis; equilibration; forskolin; natural product analogues